PROBLEM BASED INSTRUCTION SEBAGAI ALTERNATIF MODEL PEMBELAJARAN FISIKA DI SMA - Prayekti -- (Jurnal Pendidikan dan Kebudayaan, 2010)
This research was conducted to prove the PBI model can improve learning outcomes, activities and responses of students in learning. The model is applied to two classes XI of High school in South Jakarta. The first is class-XI of IPA1 and the other is class-XI of IPA2. IPA1 given treatment by applying PBI learning model, while for class-XI IPA2 performed as conventional classical learning. After the application of learning models obtained PBI’s first treatment of Class-XI of IPA1 average value for the lowest pretes is 3.25 while the average value is the highest 6.75. Meanwhile, for class-XI of IPA2, value of the lowest average is 3.25 and the highest is 6.25. Posttes for first-class average score is 6.45 and the lowest the highest is 8.75, whereas for class XI posttes value IPA2 lowest average is 6.75 and the highest value of 9.00. In the second treatment available, IPA1 class-XI, the average value of the lowest student score is 5.00 and the highest average is 7.35, while for class-XI IPA2 average value is 6.45 the lowest and the highest is 8.5. In the third treatment results obtained pretes average grade XI of IPA1 lowest and the highest 3.25 for 4.25. and the average value posttes students obtained the lowest IPA1 is 7.25 and the highest 9.75. For class-XI IPA2 average score of students in the lowest pretes is 3.00 and the highest is 4.5. While the value posttes lowest average is 7.00 and the highest is 9.00. At first teachers were not used but the implementation of the third treatment teachers have mastered the learning model PBI well. Teachers have been able to design a model of the PBI with a good learning, teachers have been able to motivate students actively involved in problem-solving activities, define and organize learning tasks and determine the steps to solve the problem. Teachers motivate students to do reflection, and have been able to evaluate the process of investigations conducted so that students can understand their weaknesses and shortcomings of the reflection done. ABSTRAK  Penelitian ini dilakukan untuk membuktikan model Problem Based Instructional (PBI) dapat meningkatkan hasil belajar, aktivitas dan respon siswa dalam pembelajaran. Model diterapkan pada 2 kelas XI paralel SMA Swasta di Jakarta Selatan. kelas XI IPA1 dan kelas XI IPA2 Siswa kelas XI IPA1 diberikan treatment dengan menerapkan model pembelajaran PBI sedangkan untuk kelas XI IPA2 dilakukan pembelajaran klasikal seperti biasa. Hasil penerapan model pembelajaran PBI treatment pertama diperoleh hasil Kelas XI IPA1 nilai rata-rata terendah untuk pretes 3,25 sedangkan nilai ratarata tertinggi 6,75. Sementara itu untuk kelas XI IPA2 nilai rata-rata terendah 3,25 dan tertinggi 6,25. Postes untuk kelas pertama nilai rata-rata terendah 6,45 dan tertinggi 8,75, sedangkan postes untuk kelas XI IPA2 nilai rata-rata terendah 6,75 dan nilai tertinggi sebesar 9,00. Pada treatment kedua kelas XI IPA1, nilai rata-rata siswa terendah 5,00 dan nilai rata-rata tertinggi 7,35, sedangkan kelas XI IPA2 nilai rata-rata terendah 6,45 dan tertinggi 8,5. Pada treatment ketiga hasil pretes diperoleh nilai rata rata siswa kelas XI IPA1 terendah 3,25 dan tertinggi 4,25. Nilai rata-rata postes terendah yang diperoleh siswa 1 adalah 7,25 dan tertinggi 9,75. Untuk kelas XI IPA22 nilai rata-rata siswa pada pretes terendah 3,00 dan tertinggi 4,5 sedangkan nilai postes rata-rata terendah 7,00 dan tertinggi 9,00. Pada akhirnya, guru dapat merancang model pembelajaran PBI dengan baik dan dapat memotivasi siswa terlibat aktif pada kegiatan pemecahan masalah, mendefinisikan dan mengorganisasikan tugas belajar serta menentukan langkah-langkah memecahkan masalah.